Pregunta
upstudy study bank question image url

Find the derivative of the function \( B(t)=\sqrt[3]{\frac{t}{3 t^{2}+4}} \)

Ask by Vaughan Bartlett. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The derivative of \( B(t) = \sqrt[3]{\frac{t}{3t^2 + 4}} \) is: \[ B′(t) = \frac{4 - 3t^2}{3 \cdot t^{2/3} \cdot (3t^2 + 4)^{4/3}} \]

Solución

We are given the function   B(t) = ∛(t/(3t² + 4)) = [t/(3t² + 4)]^(1/3). To find its derivative B′(t), we will use the chain rule along with the quotient rule. Follow these steps: Step 1. Write B(t) as a power function:   B(t) = [u(t)]^(1/3),  where u(t) = t/(3t² + 4). By the chain rule,   B′(t) = (1/3) [u(t)]^(1/3 − 1) · u′(t) = (1/3) [u(t)]^(–2/3) · u′(t). Step 2. Compute u′(t) using the quotient rule. Recall that if u(t) = f(t)/g(t), then   u′(t) = [g(t) f′(t) − f(t) g′(t)] / [g(t)]². Here, f(t) = t and g(t) = 3t² + 4, so   f′(t) = 1  and  g′(t) = 6t. Thus,   u′(t) = [(3t² + 4)(1) − t(6t)] / (3t² + 4)²        = [3t² + 4 − 6t²] / (3t² + 4)²        = (4 − 3t²) / (3t² + 4)². Step 3. Substitute u(t) and u′(t) back into the expression for B′(t):   B′(t) = (1/3) [t/(3t² + 4)]^(–2/3) · [(4 − 3t²)/(3t² + 4)²]. To simplify the expression [t/(3t² + 4)]^(–2/3), note that a negative exponent inverts the fraction:   [t/(3t² + 4)]^(–2/3) = (3t² + 4)^(2/3)/t^(2/3). Now substitute this back:   B′(t) = (1/3) · [(3t² + 4)^(2/3)/t^(2/3)] · [(4 − 3t²)/(3t² + 4)²]. Combine the factors involving (3t² + 4):   (3t² + 4)^(2/3) / (3t² + 4)² = 1/(3t² + 4)^(2 − 2/3) = 1/(3t² + 4)^(4/3). Thus, the derivative simplifies to:   B′(t) = (1/3) · (4 − 3t²) / [t^(2/3) (3t² + 4)^(4/3)]. So the final answer is:   B′(t) = (4 − 3t²) / [3 · t^(2/3) · (3t² + 4)^(4/3)].

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To find the derivative of the function \( B(t)=\sqrt[3]{\frac{t}{3t^{2}+4}} \), we can apply the chain rule and the quotient rule. Let \( u = \frac{t}{3t^{2}+4} \). Then, we can rewrite the function as \( B(t) = u^{1/3} \). 1. Differentiate \( B(t) \) using the chain rule: \[ B'(t) = \frac{1}{3} u^{-2/3} \cdot u' \] 2. Next, we find \( u' \) using the quotient rule: \[ u' = \frac{(3t^2+4)(1) - t(6t)}{(3t^2+4)^2} \] Simplifying this gives: \[ u' = \frac{3t^2+4 - 6t^2}{(3t^2+4)^2} = \frac{-3t^2 + 4}{(3t^2+4)^2} \] 3. Now substitute \( u' \) back into the derivative of \( B(t) \): \[ B'(t) = \frac{1}{3} \left( \frac{t}{3t^2+4} \right)^{-2/3} \cdot \frac{-3t^2 + 4}{(3t^2+4)^2} \] 4. Finally, putting it all together: \[ B'(t) = \frac{-1}{3} \cdot \frac{-3t^2 + 4}{3} \cdot \frac{(3t^2 + 4)^{-2/3}}{(3t^2 + 4)^2} \] This simplifies to: \[ B'(t) = \frac{(-3t^2 + 4)}{3(3t^2 + 4)^{5/3}} \] So, the derivative is: \[ B'(t) = \frac{4 - 3t^2}{3(3t^2 + 4)^{5/3}} \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad